Increased charcoal yield & production of lighter oils from the slow pyrolysis of biomass - Russell, Scott; Turrion-Gomez, Juan Luis; Meredith, Will; Langston, Paul A.; Snape, Colin E. (Elsevier, 2017)
In an effort to reduce CO2 emissions from solid fuels, a considerable amount of research is going into how improve the manufacturing processes and product properties of the products from pyrolysis. One aspect that is often overlooked is the production of charcoal for cooking and soil remediation, which is an inefficient conversion process. There is considerable interest into using additives to increase charcoal yields, and based on the observation from fast pyrolysis work that certain catalyst tar cracking pathways can deposit considerable amounts of coke on the surface of the catalyst, there is a potential application to slow pyrolysis processes producing charcoal. Alumino-silicate catalysts have been shown to have a relatively high tendency to do this. This work hypothesises that this catalysation can be applied to slow pyrolysis, with low cost alumino-silicate minerals, specially bentonite clay, which has been added to pine pyrolysis in concentrations up to 60% wt (against input biomass) at temperatures 300–700 °C.